The Application of Ethnographic Studies in the Management of South-South Interstate Boundaries of Nigeria - Oji, Okechukwu Richard (SOUTH EAST JOURNAL OF POLITICAL SCIENCE, 2021)
Boundary disputes in the SOUTH-SOUTH (SS) Zone and the frequent conflicts exhibited along the interstate and inter-zonal boundaries of Nigeria have lingered for some time now. The paper argues that poor governance, poor infrastructural development, increased agitations for resource control, restiveness of minority ethnic groups and perceived domination by majority groups are some of the kick factors in boundary disputes in the SS Zone. The paper posits that the inability to set up an investigation team that would traverse the boundary corridor and recommend enabling and effective boundary management strategies further aggravates boundary disputes in the Zone, and recommends that the conduct of ethnographic studies by the National Boundary Commission (NBC) should be considered as part of the activities and Policy enablers in Boundary definition and management.